2016
DOI: 10.1038/srep36273
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation of guilt for everyday moral transgressions: The role of the anterior insula and the influence of interpersonal psychopathic traits

Abstract: Psychopathy is a personality disorder characterised by atypical moral behaviour likely rooted in atypical affective/motivational processing, as opposed to an inability to judge the wrongness of an action. Guilt is a moral emotion believed to play a crucial role in adherence to moral and social norms, but the mechanisms by which guilt (or lack thereof) may influence behaviour in individuals with high levels of psychopathic traits are unclear. We measured neural responses during the anticipation of guilt about c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Several studies implicated dysfunction of the limbic system in psychopathy in the context of moral evaluations (59,63,99,101,114). Activity in the anterior insular cortex, which modulates anticipated guilt, was attenuated in psychopathic subjects, and the activity negatively correlated with interpersonal psychopathic traits (98).…”
Section: Moralitymentioning
confidence: 99%
“…Several studies implicated dysfunction of the limbic system in psychopathy in the context of moral evaluations (59,63,99,101,114). Activity in the anterior insular cortex, which modulates anticipated guilt, was attenuated in psychopathic subjects, and the activity negatively correlated with interpersonal psychopathic traits (98).…”
Section: Moralitymentioning
confidence: 99%
“…They are also highly strategic (Jones and Paulhus, 2012 ) and this bring them to a great deal of deception during their everyday life (Kashy and DePaulo, 1996 ). Similarly, psychopaths are more likely to perform premeditated (deliberate) than impulsive crimes (Swogger et al, 2010 ), and show a weaker modulation of anticipated guilt in anterior insula (Seara-Cardoso et al, 2016 ).…”
mentioning
confidence: 99%
“…Third, we did not distinguish the lateral and medial side of the orbitofrontal cortex, which are supposed to have separate roles (Stalnaker et al ., ). While Wagner, N'Diaye, Ethofer, and Vuilleumier () reported that guilt episodes specifically recruited the right lateral orbitofrontal cortex, the regions found most consistently in functional MRI studies to be associated with guilt are the frontopolar cortex (Broadmann area 10) (Kédia, Berthoz, Wessa, Hilton, & Martinot, ; Moll et al ., ; Seara‐Cardoso et al ., ; Takahashi et al ., ; Zahn, de Oliveira‐Souza, et al ., ; Zahn, Moll, et al ., ) and the subgenual and adjacent subcortical septal region (Basile et al ., ; Green, Lambon Ralph, Moll, Deakin, & Zahn, ; Zahn, de Oliveira‐Souza, et al ., ; Zahn, Moll, et al ., ). However, the number of patients in the present study was not large enough to distinguish the lateral and medial side of the orbitofrontal cortex Fourth, no perfusion measures to ensure functioning of the non‐lesioned area were carried out, and thus, there might have been some non‐lesioned cortices with functional depression that was not detected in our study.…”
Section: Discussionmentioning
confidence: 97%